Financial Aspects of Offshore Activities - Fielden, John (International Higher Education, 2013)
This article analyses the experience of 24 universities in setting up and operating offshore campuses and transnational education activities. It focuses on the financial aspects including their relationship with commercial partners and the potential for making surpluses.